649Personal history of keratinocyte carcinoma is a marker of inherited cancer risk: Mendelian randomization analyses. (2nd September 2021) - Dusingize, Jean Claude; Olsen, Catherine; An, Jiyuan; Liyanage, Upekha; Pandeya, Nirmala; Law, Matthew; Neale, Rachel; Ong, Jue-Sheng; MacGregor, Stuart; Whiteman, David
Abstract: Background: A personal history of keratinocyte carcinoma (KC) has been reported as a risk factor for developing subsequent primary cutaneous and non-cutaneous malignancies. However most evidence to date stems from observational studies which are prone to bias, confounding and reverse causation. Our aim was to examine this association using different Mendelian randomization (MR) approaches. Methods: We performed a one-sample MR analysis using individual-level data from the UK Biobank (n = 394, 306). This analysis was then validated in an independent dataset in the QSkin cohort (n = 16, 896). Using 64 independent genetic variants known to be associated with KC, we generated a polygenic risk score (PRS) for each participant in the UK Biobank and the QSkin cohort. We then performed two-sample MR analyses using genome-wide association study (GWAS) summary statistics. We tested the association between genetically predicted KC and risk of subsequent cancer using logistic regression. Results: Results from one-sample MR analyses in the UK Biobank indicated that a personal history of KC was significantly associated with cancer overall (excluding melanoma) (OR: 1.15, 95% CI: 1.10-1.20, per doubling the prevalence of KC). The results from the two-sample MR corroborate the findings from the one-sample MR, although the risk estimate was lower (OR: 1.05, 95% CI: 1.03-1.07). Conclusions: Our MR analyses suggest that genetically predicted KC is a risk factor for developing subsequent primary malignancies. Key messages: A personal history of KC may serve as a proxy marker of inherited cancer risk.